A community-based physical therapy program focused on education and therapeutic exercises to reduce pain and improve independence among the elderly at the Bhakti Luhur Tropodo Nursing Home - Krisnaudi, Adiya Rindi; Astuti, Martha Sri; Anggarani, Anastasia Putu Martha; Lase, Oktaviani Masditaria (Darmabakti: Jurnal Pengabdian kepada Masyarakat, 2026)
This community service initiative was motivated by the high prevalence of musculoskeletal disorders among the elderly, particularly knee pain and lower back pain, which lead to a decline in functional capacity and independence. The objectives of this initiative are to enhance knowledge, reduce pain intensity, and improve the functional abilities of the elderly through a community-based physical therapy program. The methods used included health education, demonstrations of therapeutic exercises, and individualized exercise guidance. The interventions provided consisted of strengthening and flexibility exercises such as quadriceps sets, straight leg raises, heel slides, knee extensions, and bridging, as well as exercises for low back pain such as single knee to chest and double knee to chest. Evaluation was conducted through pre- and post-tests of knowledge and pain measurement using the Numeric Rating Scale (NRS). Results showed an increase in knowledge in the “good” category from 49% to 76%, as well as a reduction in severe knee pain from 23% to 6% and in back pain from 32% to 4%. Additionally, there was an improvement in the elderly participants’ ability to perform independent exercises, as well as an increased role for caregivers in supporting the elderly. This program effectively enhances physical, cognitive, and behavioral functioning, thereby contributing to sustained improvements in the quality of life for the elderly.